Pengaruh Penambahan Tepung Tempe pada Sosis Daging Ayam terhadap Uji Daya Terima dan Kandungan Gizi - novrianti, Eka; Wulan Dari, Dini; Mursyid, Mursyid (3031-8572, 2024)
Sausage is a processed food product made from a mixture of meat that is inserted into a sausage casing. One of the innovations that can be developed is the addition of tempeh flour which is expected to provide a different taste so that it can increase the acceptability and nutritional content of the sausage. The purpose of this study was to determine the acceptability of consumers (color, aroma, taste, and texture), as well as to determine the levels of protein, fat, carbohydrates, fiber, water content and ash content. This study is a quantitative study, with an experimental design. This study used a completely randomized design (CRD) with 5 treatments (addition of tempe flour in the amount of 0%, 5%, 10%, 15% and 20%). This research was conducted in January 2022 at the Nutritional Laboratory of Stikes Baiturrahim Jambi and the nutritional content test was carried out at the Laboratory of the Faculty of Animal Husbandry, Jambi University. Acceptability parameters (hedonic quality test), color, aroma, texture and taste with the help of 30 consumer panelists. This study used the One-Way ANOVA data analysis method and the Tukey test with a standard < 0.05. And then proceed with the nutritional content test. Based on the results of the panelist test, it is known that the most preferred is the addition of tempe flour as much as 20% (A5) in terms of color, aroma, taste and texture. With a protein content of 8.15%, fat content of 3.72%, carbohydrate content of 23.60%, fiber content of 1.98%, water content of 54.67% and ash content of 9.85%. There is a significant effect on the manufacture of chicken sausage with the addition of tempeh flour on the acceptability and nutritional content